Colloidal Quantum Dot Light Emitting Diodes at Telecom Wavelength with 18% Quantum Efficiency and Over 1 MHz Bandwidth. Issue 20 (4th May 2022) - Pradhan, Santanu; Dalmases, Mariona; Taghipour, Nima; Kundu, Biswajit; Konstantatos, Gerasimos
Abstract: Developing high performance, low‐cost solid‐state light emitters in the telecom wavelength bandwidth is of paramount importance for infrared light‐based communications. Colloidal quantum dot (CQD) based light emitting diodes (LEDs) have shown tremendous advances in recent times through improvement in synthesis chemistry, surface property, and device structures. Despite the tremendous advancements of CQD based LEDs in the visible range with efficiency reaching theoretical limits, their short‐wave infrared (SWIR) counterparts mainly based on lead chalcogenide CQDs, have shown lower performance (≈8%). Here the authors report on highly efficient SWIR CQD LEDs with a recorded EQE of 11.8% enabled by the use of a binary CQD matrix comprising QD populations of different bandgaps at the emission wavelength of 1550 nm. By further optimizing the optical out‐coupling via the use of a hemispherical lens to reduce optical waveguide loss, the EQE of the LED increased to 18.6%. The CQD LED has an electrical bandwidth of 2 MHz, which motivated them to demonstrate its use in the first SWIR free‐space optical transmission link based entirely on CQD technology (photodetector and light emitter) opening a new window of applications for CQD optoelectronics. Abstract : The authors report infrared PbS colloidal quantum dot (CQD) LEDs emitting at 1550 nm with an external quantum efficiency of 18% and 1 MHz bandwidth response via optimizing the composition of the CQD charge supply matrix. They further demonstrate a proof‐of‐concept optical infrared wireless data transfer scheme using a LED and photodetector based entirely on CQD technology.